Single-machine scheduling with machine unavailability periods and resource dependent processing times - Shabtay, Dvir (European journal of operational research, 2022)
•We study a single-machine scheduling problem with a machine-unavailability period.•Processing times are resource-dependent.•The problem is known to be NP-hard.•We focus on the design of pseudo-polynomial time and approximation algorithms.•Extension to the case of a fixed number of unavailability periods is provided. We study a single-machine scheduling problem, where each of the job processing times is a bounded linear decreasing function of the amount of resource allocated to its processing operation, and there is a single and fixed machine-unavailability interval that begins at time T. A solution is given by (i) partitioning the jobs into two sets, corresponding to the set of jobs to be processed before and after the unavailability period; and (ii) defining the amount of resource allocated to the processing operation of each of the jobs. A solution is feasible if the total processing time of all jobs assigned to be processed before the unavailability period does not exceed T. Our aim is to find a feasible solution that minimizes the makespan plus the total resource consumption cost. As the problem is known to be NP-hard even for constant processing times, we focus on the design of pseudo-polynomial time and approximation algorithms. Extension to the case of a fixed number of unavailability intervals is also provided.